Sosialisasi Literasi Digital dan Etika Online Dalam Bisnis Berdasarkan UU ITE di SMA Dian Andalas Padang - Aulia Fikrina; Kiki Sarianti; Yolanda Desti; Mutia Jawaz Muslim; Yossiramah Sucia; Meissy Putri Deswari; Ramadhi Ramadhi; Tri Icha Fauziah; Reki Reki (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Digital literacy is an essential skill in the digital era, especially for the younger generation who are starting to actively engage in entrepreneurship through online platforms. However, students' understanding of online ethics and legal frameworks such as the Electronic Information and Transaction Law (UU ITE) is still limited. This community service activity aims to improve the digital literacy of Dian Andalas Padang High School students, with a focus on online ethics in law-based digital business. The methods used include interactive lectures, group discussions, and case simulations to provide a deep and applicative understanding. The results of this activity showed a significant increase in students' understanding of digital literacy and the implementation of the ITE Law. Case discussions and simulations help students identify common violations of the law in online businesses, such as fraud and the spread of false information, and understand how to prevent them. The positive response from students and teachers emphasized the importance of this activity in equipping the younger generation with ethical and law-abiding digital skills, while encouraging schools to integrate law-based digital literacy into the curriculum.